(untitled) (Bangladesh Journal of Plastic Surgery, 2014)
We are reporting a case of recurrent soft tissue tumor over the chest wall-histologically proven Dermato fibrosarcoma protuberance. Wide surgical excision with reconstruction is recommended for improvement of quality of life and prolong survival. DOI: http://dx.doi.org/10.3329/bdjps.v3i2.18252 Bangladesh Journal of Plastic Surgery July 2012, 3(2): 53-56